Similar long-term recurrence rates with cystectomy and CO2 laser vaporization for endometrioma: a retrospective study. Issue 1 (July 2022) - Bafort, Celine; Mourad Tawfic, Nada; Meuleman, Christel; Laenen, Annouschka; Timmerman, Dirk; Van Schoubroeck, Dominique; Tomassetti, Carla
Highlights: CO2 laser vaporization is a safe alternative to cystectomy for endometrioma. CO2 laser vaporization does not increase the recurrence rate of endometrioma. CO2 laser vaporization has equally high post-operative pregnancy rates as cystectomy for endometrioma. Abstract: Research question: Is there a difference in recurrence rate of endometrioma(s) after cystectomy versus CO2 laser vaporization of the cyst wall? Design: This single-centre retrospective study included 270 patients undergoing laparoscopic surgery for endometriomas between January 2010 and December 2014, stratified according to the surgical technique used. All 270 included patients underwent complete laparoscopic surgery for endometrioma(s): 155 underwent cystectomy, 63 complete CO2 laser vaporization of the cyst wall and 52 a mixed technique. The primary outcome studied was the difference in recurrence rate between the cystectomy group and the CO2 laser vaporization group. Results: The mean duration of follow-up was 58 (±34) months. Imaging-based recurrence (any cyst size) was reported in 9.9% of patients ( n  = 12/121) treated with cystectomy and in 13.3% of patients ( n  = 6/45) who underwent a vaporization ( P  = 0.577). The need for reintervention for endometrioma(s) was also similar in both groups, with a rate of 3.2% ( n  = 5/155) after cystectomy and 4.8% ( n  = 3/63) after vaporization ( P  = 0.476). Of 160 women who wanted to conceive immediately after surgery, 73.8% became pregnant (72.6% [77/106] in the cystectomy group and 75.9% [41/54] in the vaporization group [ P  = 0.310]). Conception occurred mostly by assisted reproductive technology (57.1% [44/77] in the cystectomy group and 70.7% [29/41] in the vaporization group [ P  = 0.074]). Conclusions: Similar rates of recurrence for endometrioma(s) were observed after cystectomy versus CO2 laser vaporization. As other studies have suggested that CO2 laser vaporization may be less harmful to the normal ovarian tissue, it can be considered as a safe alternative for cystectomy in women wishing to preserve their reproductive potential.